(untitled) (International Journal of Scientific Trends, 2024)
In this article, the factors affecting the economic indicators of a mining enterprise in the extraction of minerals are studied and analyzed in detail. Based on the analysis, the importance of indicators of loss and dilution not only in the economy of the enterprise, but also the socio-environmental impact is highlighted. It is also noted that reducing the indicators of loss and dilution is the most optimal way to increase the productivity of a mining enterprise.